Antinociceptive effects of the adenylyl cyclase inhibitor ST034307 on tooth-movement-induced nociception in rats. (February 2019) - Cheng, Yangfan; Huang, Peina; Meng, Bowen; Gan, Lei; Wu, Dongle; Cao, Yang
Highlights: Tooth movement was associated with enhanced cAMP generation and PKA activation. Injection of a selective AC1 inhibitor decreased mouth wiping and RGS scores. ST034307 can be an effective pharmacotherapy for orthodontic nociception. Abstract: Objective: This study aimed to investigate the antinociceptive effects of the selective adenylyl cyclase type 1 (AC1) inhibitor ST034307 on tooth movement nociception through orofacial nociceptive behavior tests and molecular examination. Methods: We placed fixed nickel-titanium alloy closed-coil springs around the incisors of male Sprague-Dawley rats to induce tooth movement. We subsequently administered ST034307 (3 mg/kg), for 2 days, intraperitoneally, and then subjected the rats to a battery of behavioral tests (n = 10/group) to assess orofacial nociception. The changes in the expression of key molecules in the anterior cingulate cortex were measured by ELISA (n = 8/group) and Western blotting (n = 8/group). Results: Tooth movement increased face-grooming activities and rat grimace scale scores. Tooth movement was also associated with enhanced cyclic adenosine monophosphate (cAMP) generation as well as protein kinase A (PKA) activation. Moreover, the phosphorylation of alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors and expression of N-methyl-d-aspartate (NMDA) receptors in the anterior cingulate cortex increased during tooth movement. ST034307 significantly decreased mouth wiping and rat grimace scale scores, accompanied by reductions in cAMP generation, PKA activation, AMPA receptor phosphorylation, and NMDA receptor expression in the anterior cingulate cortex. Conclusions: These results suggest that adenylyl cyclase type 1 plays an important role in the development of orthodontic tooth movement nociception. Furthermore, ST034307 can be used as an effective pharmacotherapy for orthodontic nociception.